Abdominal adiposity contributes to adverse glycemic control and albuminuria in Chinese type 2 diabetic patients: A cross‐sectional study: 中国2型糖尿病患者腹部脂肪蓄积与血糖控制不佳及蛋白尿风险显著相关. (20th July 2016) - Wang, Zhengyi; Ding, Lin; Huang, Xiaolin; Chen, Ying; Sun, Wanwan; Lin, Lin; Huang, Ya; Wang, Po; Peng, Kui; Lu, Jieli; Chen, Yuhong; Xu, Min; et al.
Abstract: Background: Abdominal adipose tissue plays an important role in the development of type 2 diabetes. However, few data have suggested its role in the prognosis of diabetes. This study aimed to investigate the association between waist‐hip ratio (WHR), glycemic control, and early nephropathy in Chinese type 2 diabetic patients. Methods: A cross‐sectional study was conducted in 1709 previously‐ and newly‐diagnosed diabetic patients nested in a cohort study consisting of 10 375 participants aged ≥40 years in Shanghai, China. General characteristics through questionnaire, anthropometric measures, and biochemical results were recorded. Statistical analysis was performed by SPSS v20.0. Results: Each quartile increase in WHR was significantly associated with a fasting plasma glucose (FPG) ≥ 126 mg/dl [OR (95% CI):1.18 (1.06–1.30)], an HbA1c ≥ 7.0% [1.21 (1.08–1.35)], and a HOMA‐IR ≥ 2.5 [1.30 (1.16–1.46)] after multivariable adjustments. WHR was not associated with a 2h PG ≥ 200mg/dl [1.13 (0.97–1.31)]. The risk for increased albuminuria (UACR ≥10.18mg/g) was also significantly associated with higher WHR after adjustment for HbA1c [1.14 (1.02–1.27)]. However, no significant relationship was seen between WHR and an estimated glomerular filtration rate < 90 ml/min per 1.73 m 2 . Interactions of sex, or physical activity with WHR in association with glycemic control and increased albuminuria were found ( P values for interaction <0.05). Conclusions: These data demonstrated an independent role of abdominal adipose tissue in glycemic control and renal complications of type 2 diabetes. Interventions aiming to reduce abdominal adipose tissue may have additional benefits. Abstract : Prevalence of elevated glucose levels and insulin resistance (Panel A), and increased albuminuria and decreased eGFR (Panel B) across quartiles of waist‐hip ratio in Chinese type 2 diabetic patients. P for trend for each outcome was presented.FPG: fasting plasma glucose; 2h PG: 2h post‐load plasma glucose; HbA1c: glycated hemoglobin A1c; HOMA‐IR: index of homeostasis model assessment of insulin resistance; UACR: urinary albumin‐to‐creatinine ratio; eGFR: estimated glomerular filtration rate.